1978
DOI: 10.1111/j.1365-2621.1978.tb09756.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Properties of the Aroma of Beef Cooked Conventionally and by Microwave Radiation

Abstract: Sensory properties of the aroma of cooked beef were analyzed using an odor quality assessment technique based on, though not identical with, that of Persson et al. (1973a) (J. Food Sci. 38: 386). Detailed odor descriptions were obtained for beef samples cooked conventionally and by microwave radiation for different periods of time. Several differences in aroma characteristics were observed. In general, odor qualities rated highly for the aroma of microwave cooked beef were shown to be either associated with "m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Only three of the eight studies cited in Table 1 involved chicken. Although some of the terms listed were derived by the sensory panels used in those studies, MacLeod and Coppock (1978) and Persson et al (1973) were the only researchers focusing on the terminology and panel use of the terms rather than citing the terms as the means of focusing on treatment of process variations.…”
Section: Resultsmentioning
confidence: 99%
“…Only three of the eight studies cited in Table 1 involved chicken. Although some of the terms listed were derived by the sensory panels used in those studies, MacLeod and Coppock (1978) and Persson et al (1973) were the only researchers focusing on the terminology and panel use of the terms rather than citing the terms as the means of focusing on treatment of process variations.…”
Section: Resultsmentioning
confidence: 99%
“…This latter function was assisted by a list of flavour descriptors (developed from MacLeod & Coppock, 1978). The tasting was conducted as a group session, each panelist individually scoring and describing each sample followed by a group discussion after all samples had been tasted.…”
Section: Trainingmentioning
confidence: 99%
“…Using Quantitative Descriptive Analysis, Meltqn et al (1982) reported ground beef descriptors, including fishy, metallic, milky, oily, sheepy, sweet, and stale. MacLeod and Coppock (1978) reported cooked beef aroma descriptors, including animal, blood, fragrant, sharp, pungent, and sickly. Many off-odor compounds form during autoxidation of unsaturated fatty acids, including oleic, linoleic, linolenic, and arachidonic acids.…”
Section: Introductionmentioning
confidence: 99%